The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.3390/s90806219
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of Micromirror Arrays Using a CMOS-MEMS Technique

Abstract: In this study we used the commercial 0.35 μm CMOS (complementary metal oxide semiconductor) process and simple maskless post-processing to fabricate an array of micromirrors exhibiting high natural frequency. The micromirrors were manufactured from aluminum; the sacrificial layer was silicon dioxide. Because we fabricated the micromirror arrays using the standard CMOS process, they have the potential to be integrated with circuitry on a chip. For post-processing we used an etchant to remove the sacrificial lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…With a platform’s dimension of 1.4 mm × 1.7 mm, the performances of the device are at 0.3° on two axes at 55 V with a resonant frequency of 181 Hz and 45 Hz for outer frame and mirror respectively. Moreover, surface electrostatic actuators can perform up to three DOFs by using a CMOS technique [ 54 ]. For a tip-tilt-piston stage, Kao et al reported an electrostatic phenomenon of parallel plates.…”
Section: Actuation Principlesmentioning
confidence: 99%
“…With a platform’s dimension of 1.4 mm × 1.7 mm, the performances of the device are at 0.3° on two axes at 55 V with a resonant frequency of 181 Hz and 45 Hz for outer frame and mirror respectively. Moreover, surface electrostatic actuators can perform up to three DOFs by using a CMOS technique [ 54 ]. For a tip-tilt-piston stage, Kao et al reported an electrostatic phenomenon of parallel plates.…”
Section: Actuation Principlesmentioning
confidence: 99%
“…Besides DC biasing, MEMS sensors often require accurate control voltages, as well. A DC voltage programmable between 5 V and 45 V was used in [10] to control the tilting angle of micromirrors between 0.24°and 2.55°; in [11], DC voltages up to 30 V were applied to the top or middle membranes of capacitive mass-based MEMS sensors, to enhance their operational properties, particularly their sensitivity. MEMS varicaps have similar requirements: the voltage levels used in [12] varied from 10 V to 22 V, while in [13], the range was from 0 to 20 V.…”
Section: Introductionmentioning
confidence: 99%
“…However, the continuous quest for size and cost reduction demands MEMS devices to work in conjunction with integrated circuits manufactured in low-cost CMOS processes and even to be realized on the same CMOS substrate-the CMOS MEMS monolithic integration [18]. Complex MEMS devices can be integrated alongside electronic circuitry in a standard CMOS process, with only mask-less post-CMOS processing [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturing technique which uses the commercial CMOS process to fabricate MEMS devices is called CMOS-MEMS [ 14 16 ]. Micro devices made by the CMOS-MEMS technique usually need a post-process to coat the functional films [ 17 ] or to release the suspended structures [ 18 ]. For example, Liu et al [ 17 ] coated a sensitive film of polyaniline nanofiber on a micro ammonia sensor using a post-process.…”
Section: Introductionmentioning
confidence: 99%